An investigation of AASHTO's requirements for providing continuity in simple span bridges made continuous. (1st March 2018) - Menkulasi, Fatmir; Patel, Al; Baghi, Hadi
Highlights: AAASHTO's requirements for providing continuity are investigated. Ages for when continuity can be established are provided for various configurations. A method to conduct time dependent analysis and calculate restraint moments is presented. The influence of adopted creep and shrinkage models on restraint moments is examined. Higher beam compressive strengths at release result in lower required continuity ages. Abstract: AASHTO's requirements for providing continuity in simple span bridges made continuous are investigated by performing a parametric study which consists of 140 time dependent analyses for various precast concrete beam shapes. The beam shapes considered include three precast concrete bulb tees (PCBT), two AASHTO type beams, and two Florida I-beams (FIB). Various beam spacing and span configurations are considered. A sectional analysis approach that employs the age adjusted effective modulus method for capturing creep effects is presented for calculating restraint moments. AASHTO models for creep and shrinkage are used to conduct the parametric study. For each case considered a minimum girder age for when continuity can be established is recommended such that the total restraint moment at the intermediate support is equal to or smaller than zero. The recommended minimum girder ages at continuity vary from 55 to 90 days for PCBTs, 55–70 days for AASHTO type beams, and 55–80 days for FIBs. The influence of f ci ′, choice of creep and shrinkage model, and choice of analysis method on the magnitude of restraint moments is investigated. The specification of a higher f ci ′ is an effective technique to reduce the minimum required girder age at continuity. The magnitude of restraint moments appears to be highly sensitive to the selected creep and shrinkage model. The proposed analysis method addresses the shortcomings of other closed form formulations and results in restraint moments that are more sensitive to the girder age at continuity.